Influences of Different Operative Methods on the Recurrence Rate of Non-Muscle-Invasive Bladder Cancer - Li, shoubin; Jia, Yi; Yu, Chunhong; Xiao, Helong; Guo , Liuxiong; Sun, Fuzhen; Wei, Dong; Zhang , Panying; Li, Jingpo; Liu, Junjiang (Urology Journal, 2020)
Purpose: To compare the influence of three operative approaches [transurethral en bloc resection of bladder tumor by pin-shaped electrode (pin-ERBT), transurethral resection of bladder tumor (TURBT) and transurethral holmium laser resection of bladder tumor (HoLRBT)] on the recurrence rate of non-muscle-invasive bladder cancer (NMIBC) at low dimension (i.e. diameter below 3 cm). Materials and Methods: A retrospective analysis was conducted for a total of 115 patients affected by solitary NMIBC, with a diameter <3 cm, who were submitted to operation between March 2013 to May 2017. The patients were divided according to the operative method applied (pin-ERBT, TURBT and HoLRBT groups, respectively). The 2-year recurrence rate was compared among the three groups, and multivariat Cox hazard model analysis was applied to analyze the influencing factor(s) for postoperative recurrence. Results: The 2-year recurrence rate was 10.0% in ERBT, 38.5% in TURBT and 40.0% in HoLRBT group, with a significant difference (P =0.014). According to the Cox hazard model analysis, age(HR=1.058, 95% CI: 1.019 1.098，P=0.003), operative method(HR=2.974,6.508, 95% CI: 0.862 10.255,1.657 25.566, P=0.023), smoking(HR=2.399, 95% CI: 1.147 5.017, P=0.020) and pathological grade(HR=2.012,95% CI: 1.279 3.165, P=0.002) were risk factors for postoperative recurrence of bladder cancer. Conclusion: Pin-ERBT can prominently decrease the postoperative recurrence rate of solitary NMIBC with a diameter <3 cm.